Design and Development of Food Ordering Mobile Application - Lim, Kai Yee; Md. Fudzee, Mohd Farhan (Applied Information Technology And Computer Science, 2021)
Many restaurants or cafes still apply traditional ordering methods such as writing on paper, queue up at the counter or waiter serving in Malaysia. Due to the coronavirus pandemic, people also must maintain a social distance from others. Thus, the development of food ordering application can provide a more efficient food order process for the customer, and it can also diminish contact with other people. Furthermore, the rate of obesity or overweight of Malaysian citizen still continuously increased in the past few years. So, the application also provides calorie counts features on the menu. This project developed the food ordering application using the Waterfall Software development life cycle (SDLC) methodology. This project has categorized into several modules: user registration and user login, food ordering, food cart, menu and order management module, and payment module. Android studio and Java programming languages are used to develop this application. This food ordering application was designed for Owl City Cafe Melaka, and it has achieved an expected result by doing the unit testing and some users acceptance testing. 66.67% of the performance testing fully satisfied, and 33.33% of the performance testing users were mostly satisfied. However, this application still consists of some limitations and needs improvement in future works, such as current location services.